1999
DOI: 10.1038/sj.bdj.4800156a
|View full text |Cite
|
Sign up to set email alerts
|

Dental service use and the implications for oral cancer screening in a sample of Bangladeshi adult medical care users living in Tower Hamlets, UK

Abstract: 517RESEARCH dental public health may arise de novo although in high prevalence areas such as Southern Asia it is usually preceded by a so-called precancerous lesion -a red (erythroplakia) or a white (leukoplakia) patch. 2 In India almost all oral cancers originate from leukoplakias. 3 Secondary prevention is aimed at the early recognition of oral cancer. Treatment of precancerous or small (less than 2 cm) lesions results in an improved prognosis and causes limited morbidity. 4 The UK Working Group on Screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 19 publications
1
29
1
Order By: Relevance
“…Alarmingly, this study suggests that the highest period of risk for engaging in a betel-quid, areca nut alone or mistee pan habit is between the ages of 5 and 12. This is somewhat earlier than that reported in previous research 4 for which 11-15 was cited as the most frequent age range. This difference can be interpreted to suggest that the areca nut habit amongst children with a South Asian ethnic background, but are mainly first or second generation UK born, is being engaged in earlier than amongst previous cohorts born in the South Asian countries.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Alarmingly, this study suggests that the highest period of risk for engaging in a betel-quid, areca nut alone or mistee pan habit is between the ages of 5 and 12. This is somewhat earlier than that reported in previous research 4 for which 11-15 was cited as the most frequent age range. This difference can be interpreted to suggest that the areca nut habit amongst children with a South Asian ethnic background, but are mainly first or second generation UK born, is being engaged in earlier than amongst previous cohorts born in the South Asian countries.…”
Section: Discussioncontrasting
confidence: 54%
“…Although in far smaller proportions than reported in this study, an areca nut habit has been reported to begin amongst those aged up to 50, with daily frequency of use also increasing with age. 4 The current cohort of chewers in this study is therefore likely to under represent the size of the future population engaging in an areca nut habit, although the figures are likely to reflect a high percentage of this future population. The results from this study support the British Dental Association recommendations 20 which suggest that dentists pay special attention for signs of OSF and potentially malignant lesions amongst South Asian children during routine consultations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The health survey for England 1999 met three of the 12 guidelines and partially met one other. 2 Three studies met three guidelines.…”
Section: Survey Methodsmentioning
confidence: 99%
“…Recent investigations into betel quid chewing in the UK have found the habit to be widespread among Bangladeshis [3,10]. The majority started this habit before the age of 15 years, women are more likely to use betel quid, and also more likely to add tobacco to the quid [20]. Previous studies showed that 95% of Bangladeshi women in West Yorkshire chewed betel quid, of whom 89% added tobacco [9].…”
Section: Use Of Betel Quid Among Asians In the Ukmentioning
confidence: 99%